If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + y = 480 Solving 2x + y = 480 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 2x + y + -1y = 480 + -1y Combine like terms: y + -1y = 0 2x + 0 = 480 + -1y 2x = 480 + -1y Divide each side by '2'. x = 240 + -0.5y Simplifying x = 240 + -0.5y
| 13x=5x+48 | | 2y-4=10y+36 | | 4b-3=3b+9 | | 2(x^2+60x-200)=0 | | 14x+8=6x+12 | | 2x^5-32=0 | | 2(6x-4)=27 | | log(x+12)=3 | | 2x-[X+1]=5 | | 60=15d | | cos(x)=-3.8 | | 3x-61= | | X^2-14x+17=-6x+2 | | 4(3x+6)=-38+2 | | -2tk=20 | | 6X+5X+9X=180 | | x-x^2=0.19 | | 8-(2z-9)=8-3z | | X^2+3x-24=4 | | 8x^5-196x^4+153x^3-4096x^2=0 | | 12x+1=11x+16 | | 6x-30=5(3+x) | | (X^2+5)+(x^2+4)= | | 9x-(3x+14)=16 | | 3000=(200+8x)(15-.50x) | | -12x+3+12x= | | B(b+4)=140 | | 25=48-3x | | 2p-3(2-2p)=3(p-4)-24 | | 15ab-12a= | | 6(2m-3)-3m-2m=18+m | | 5x+4=53-2x |